COULD A CONFLICT OVER THE GUARANI AQUIFER SYSTEM BE JUSTIFIED? PERSPECTIVES FROM JUST WAR THEORY AND INTERNATIONAL LAW - MARTINS CAMÕES, BEATRIZ; GONÇALVES, AUGUSTO NOBRE (Águas Subterrâneas, 2021)
This paper discusses in five sections the permissibility of a hypothetical conflict for the Guarani Aquifer resources. First, we introduce the problematic of cross-border conflict related to the usage of groundwater in South America, highlighting the importance of a conscious reflection on the morality behind resource-related conflicts. Next, we move on to a brief explanation of the modern just war theory, emphasizing its focus on just cause as a condition a conflict must meet in order to be justified from an ius ad bellum perspective. Then, we present Conway Waddington’s criticism to just war theory, together with a formulation of our hypothetical problem. In the fourth section of the paper, we defend pragmatism as a methodological approach to contemporary resource-related conflicts, for it can replace a just war theory that has prescriptive voids, and we call the reader’s attention to the fact that international law shows much influence from pragmatic thinking, setting principles that must be followed but showing concern for its historical adaptability from time to time. Finally, we draw conclusions from our analysis, and they should help the reader to maintain a positive outlook towards the theoretical and practical challenges posed to international law by water scarcity. All along, our goal is to stimulate the reader to think critically and develop his or her own assessment of those pressing moral and legal issues, hoping to raise awareness of the much problematic relation between lack of water security and imminence of armed conflict. Although we know a war is unlikely to happen in South America, we should discuss the moral, legal and humanitarian implications of water policies around the world, and instigate scientists to think of solutions for resource scarcity. This is our attempt to kick-start debate around each one’s personal responsibility for demanding fair and equal water distribution.